2015
DOI: 10.1097/icu.0000000000000184
|View full text |Cite
|
Sign up to set email alerts
|

Complications and outcomes after autoenucleation

Abstract: Autoenucleation occurs more frequently in patients with psychiatric illness or drug abuse. It can be a devastating injury, not only locally, but neurologically. Ophthalmologists should be aware of the potentially life-threatening consequences of autoenucleation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…For it is better that you lose one of your members than that your whole body be thrown into hell." Mathew 5:29 The act recommended in the Bible verse above is selfenucleation, also known as autoenucleation, which is a self-inflicted, complete removal of one's eye [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For it is better that you lose one of your members than that your whole body be thrown into hell." Mathew 5:29 The act recommended in the Bible verse above is selfenucleation, also known as autoenucleation, which is a self-inflicted, complete removal of one's eye [1].…”
Section: Introductionmentioning
confidence: 99%
“…With an average of 1 in 30 million people, autoenucleation is a rare form of self-mutilation typically associated with psychiatric disorders such as schizophrenia, substance-induced psychosis and bipolar disorder [1][2][3]. It has also been seen, though more rarely, among patients with obsessive-compulsive disorder, depression as well as mental retardation, neurosyphilis, Lesch-Nyhan syndrome or structural brain lesions [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Self-enucleation, also known as auto-enucleation or oedipism, is an uncommon type of self-mutilation that is classified as a major self-injury. [1,2] It is more common in men than in women [3,4] and is overwhelmingly associated with acute psychosis due to untreated psychiatric illnesses or drug use. [1,[4][5][6] Self-enucleation involves avulsion of the extraocular muscles, optic nerve, and ophthalmic artery (OA), which may lead to devastating neurovascular complications.…”
Section: Introductionmentioning
confidence: 99%
“…2 A review of 56 cases found that one third of the cases are bilateral. 3 The most common underlying motivations for selfenucleation are biblical interpretation, hypersexual or hyperreligious delusions, and paranoia regarding the eye.…”
Section: Introductionmentioning
confidence: 99%